HUBUNGAN ANTARA KETERAMPILAN SOSIAL DENGAN PERILAKU AGRESIF REMAJA SISWA KELAS XI SMK BUNDA KANDUNG JAKARTA SELATAN - Zeni Perdana Rizeki (Journal of Research and Measurement in Psychology, 2017)
Abstrack The purpose of this research was to know the correlation between social skills and student aggressive behavior at 10th grade of Bunda Kandung's Vocational High School in South Jakarta. This research was conducted in Bunda Kandung's Vocational High School, Pasar Minggu, South Jakarta. This research approach quantitative methods and using expost facto design. Samples of this research is 79 student with sample collection techniques are proportionate random sampling. The collecting data in this research used two instruments, namely the scale of social skills and the scale of aggressive behavior. Statistical analysis using the product moment correlation. Based on the results of data analysis found that there was a negative and significant correlation between social skills and aggressive behavior. Correlation coefficient values obtained are rxy = (-0.458) and the significance p = 0.000 <0.05 (significant), which means there is a negative and significant corelation between two variables. Keywords: social skills, aggressive behavior, adolescent